Intention to Online Shopping on Social Media - Anita Akhirruddin (Universitas Muhammadiyah Gresik, 2021)
high growth of online shopping in Indonesia gave rise to many onlien websites and platforms in Indonesia. Facebook, which is one of the social networks that many people use around the world, is one of the online selling media that is in great demand because it can reach more people. Shopping online on Facebook in addition to providing benefits for sellers and buyers. Online shopping on Facebook requires a high level of trust from buyers regarding the quality of products and serv ices, and ease in obtaining product information and payments because there are no guarantees such as online shop platforms such as shoope, tokopedia, lazada and others which before the goods are received by the customer, then the money from the buyer can not be disbursed. So researchers are interested in researching online shopping interests on the social media site facebook. The results obtained are variable trust, ease of transaction and quality of information positively affect the interest in buying online on facebook.